SOME NUMERICAL TECHNIQUES FOR SOLVING FUZZY NONLINEAR INTEGRAL EQUATION OF A FUZZIFYING FUNCTION OVER A NON-FUZZY INTERVAL - abdulqader, alan jalal (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, the basic principle and definitions for fuzzy nonlinear integral equation of a fuzzy function over a crisp interval have been discussed. The numerical technique method and some algorithmfor solving fuzzy non-linear of a fuzzy function including fuzzifying function, bunch function and LR-Type of fuzzy function over crisp domain by a computational and illustration have been developed and presented . The fuzzy nonlinear integral of fuzzy function over a crisp interval can be divided into two subsections in this paper . Some numerical examples are prepared to show the efficiency and simplicity of the methods